PERJALANAN METRO SIANTAR: DARI POS METRO HINGGA MEDIA UNGGULAN KOTA PEMATANGSIANTAR - Ellisia Heriyani; Rizqi Putra Permono; Peninna Simanjuntak; Vanesia Amelia Sebayang (Bajang Institute, 2024)
This research study is part of City History. Metro Siantar is the first local mass media published in Pematangsiantar City in 2003 under the auspices of Jawa Pos National Network. Initially known as Pos Metro Siantar, this newspaper initially reviewed crime news with sales coverage in Pematangsiantar City and Simalungun Regency. In 2006, Pos Metro Siantar changed its editorial name to Metro Siantar and shifted its focus to general daily news of the people of Pematangsiantar City and Simalungun Regency. This research uses a historical study method that includes topic selection, heuristics (collection of sources), criticism or verification of sources, interpretation, and historical historiography. The results showed that Metro Siantar played an important role as a pioneer of local mass media in Pematangsiantar City and Simalungun Regency